2016
DOI: 10.1371/journal.pone.0161458
|View full text |Cite
|
Sign up to set email alerts
|

Cold Shock Proteins Are Expressed in the Retina Following Exposure to Low Temperatures

Abstract: Hypothermia has been proposed as a therapeutic intervention for some retinal conditions, including ischemic insults. Cold exposure elevates expression of cold-shock proteins (CSP), including RNA-binding motif protein 3 (RBM3) and cold inducible RNA-binding protein (CIRP), but their presence in mammalian retina is so far unknown. Here we show the effects of hypothermia on the expression of these CSPs in retina-derived cell lines and in the retina of newborn and adult rats. Two cell lines of retinal origin, R28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 40 publications
1
23
1
7
Order By: Relevance
“…Bullfrog CIRP is 72.7% similar to mammalian CIRPs and 78.54% to Xenopus laevis ’ CIRP [ 4 ]. The amino acid sequence of CIRP in different species is shown in Figure 1 B. CIRP is ubiquitously expressed in a large variety of tissues and cells from both human and murine origins, including the brain, lungs, heart, kidneys, retinas, testis, liver, ovaries, nervous system, lymphocytes and endometrium [ 5 ]. CIRP is mainly localized in the nucleus, but can translocate to the cytoplasm under stress conditions.…”
mentioning
confidence: 99%
“…Bullfrog CIRP is 72.7% similar to mammalian CIRPs and 78.54% to Xenopus laevis ’ CIRP [ 4 ]. The amino acid sequence of CIRP in different species is shown in Figure 1 B. CIRP is ubiquitously expressed in a large variety of tissues and cells from both human and murine origins, including the brain, lungs, heart, kidneys, retinas, testis, liver, ovaries, nervous system, lymphocytes and endometrium [ 5 ]. CIRP is mainly localized in the nucleus, but can translocate to the cytoplasm under stress conditions.…”
mentioning
confidence: 99%
“…After a period of 45 min of recovery at room temperature (24 °C), some of the rats were subjected to hypothermia in a cold room (8 °C for 3 h) while the rest remained at 24 °C (normothermia). In previous studies we have shown that 3h at 8 °C produces a temperature drop in the rat of approximately 3 °C 35 . To calculate changes in retro-ocular temperature, some animals kept at normothermia (n = 5) and some animals that had just received the hypothermic treatment (n = 5) were deeply anesthetized and a thermocouple (type K, model TPK-01, Tecpel, Taiwan), connected to a digital thermometer (TES-1300, Tecpel), was placed in the orbital fossa and the temperature was rapidly recorded.…”
Section: Methodsmentioning
confidence: 85%
“…A subset of rats (n = 6 per experimental group) were sacrificed 3 h after hypothermic or normothermic treatment. The posterior chambers of the eyes were homogenized with TRIzol (Invitrogen, Madrid, Spain) and RNA was isolated and reverse transcribed as previously reported 35 . Resulting cDNA was mixed with SYBR Green PCR Master Mix (Applied Biosystems, Carlsbad, CA) for quantitative real time polymerase chain reaction (qRT-PCR) using 0.3 µM forward and reverse oligonucleotide primers (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to homologues and orthologues, CIRP has at least two paralogues: RNA‐binding motif protein 3 (RBM3)—an RNA‐binding protein up‐regulated in response to low temperature and aggrecan promoter‐binding protein‐1 (APBP‐1)—a 19‐kDa DNA/RNA‐binding protein . CIRP is constitutively and ubiquitously expressed at low levels, with studies showing its presence in the brain, lungs, heart, liver, kidneys, and endometrium, as well as in macrophages and neutrophils . Recently, both CIRP expression and release have been shown to be induced in cellular stress and inflammatory conditions .…”
Section: Cirpmentioning
confidence: 99%